2021
DOI: 10.3390/machines9010011
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a High-Frequency Dynamometer for High-Speed Milling Process

Abstract: Cutting forces are strongly associated with the mechanics of the cutting process. Hence, machining forces measurements are very important to investigate the machining process, and numerous methods of cutting forces measurements have been applied. Nowadays, a dynamometer is the most popular tool for cutting forces measurements. However, the natural frequency of a dynamometer has a direct impact on the accuracy of measured cutting forces in the machining process. Therefore, few dynamometers are appropriate and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It provides cutting forces to describe the cutting process state during machining [78]. It shows an excellent response to cutting forces due to its high reliability and sensitivity.…”
Section: Dynamometermentioning
confidence: 99%
“…It provides cutting forces to describe the cutting process state during machining [78]. It shows an excellent response to cutting forces due to its high reliability and sensitivity.…”
Section: Dynamometermentioning
confidence: 99%
“…It has shown that reducing the cutting forces can improve the tool life and decrease the tool wear [4,5]. The measurement of cutting forces is often used as an indicator in the design of a machine tool and to optimize the cutting mechanisms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Rizal et al [6], developed a force sensing system in which strain gauges were mounted on the structure and integrated to a tool holder, to monitor three cutting forces during the milling process. In other studies, a strain gauge-based torque measurement systems, called a smart tool holder, have been designed and developed.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant cutting force is divided into three components of cutting force in a simple turning operation: tangential (F C ), axial (F F ) and radial (F R ). The motive for measuring the cutting forces in machining operations comes from their major effect on cutting tool wear, cutting temperatures, the vibration mechanism and consequently the surface texture of the workpiece [12,13]. As such, cutting forces are one of the significant characteristics in machining operations [14,15].…”
Section: Introductionmentioning
confidence: 99%